Data gathering architecture for temporary worksites based on a uniform deployment of wireless sensors. (2015) - Khoufi, Ines; Mahfoudh, Saoucene; Minet, Pascale; Laouiti, Anis
Data management is an important issue in wireless sensor networks. However, the data gathering process may be unsuccessful in disconnected or random networks: some data gathered cannot be delivered to the sink, coverage holes may occur and result in missing data. To cope with this problem, we propose two distributed redeployment algorithms (distributed virtual forces algorithm (DVFA) and adaptive distributed virtual forces algorithm (ADVFA)), based on virtual forces, that provide a uniform deployment of sensor nodes. Both ensure full area coverage and network connectivity.We define a three-tier architecture where after the execution of a redeployment algorithm, sensor nodes are uniformly deployed to monitor a temporary worksite. We compute the optimal number of sensors needed to cover an area. Using this result, we parameterise DVFA and evaluate its performances. We then propose ADVFA to cope with DVFA drawbacks (e.g., node oscillations). ADVFA outperforms DVFA, considerably reducing the distance travelled by nodes and then maximising network lifetime by saving energy.